Ultrasmall single micelle@resin core-shell nanocarriers as efficient cargo loading vehicles for in vivo biomedical applications - Yang, Y.; Song, X.; Yao, Y.; Wu, H.; Liu, Jian; Zhao, Y.; Tan, M.; Yang, Q. (Royal Society of Chemistry, 2015)
Ultrasmall core–shell nanocarriers (NCs) are believed to be ideal candidates for biological applications, as proved by silica-based core–shell NCs fabricated using a single micelle as a template. Compared with inert silica, polymers with various properties play an essential and ubiquitous role in our daily life. However, the fabrication of polymer-based NCs with ultrasmall particle size (less than 20 nm) is still very limited, which is probably hindered due to the difficulty in handling the polymeric process and the soft nature of most polymers. In this study, we demonstrated the fabrication of ultrasmall single micelle@resin core–shell NCs through a single micelle template method using resorcinol–formaldehyde resins (RFRs) as model polymers. Moreover, the fluorescence properties of the ultrasmall single micelle@resin core–shell NCs could be adjusted from visible light to near-infrared through the incorporation of different dye molecules. The fluorescent single micelle@RFR core–shell NCs show extra-low cytotoxicity and great potential in both in vitro and in vivo bioimaging and photothermal therapy applications.